Development and Validation of RP-HPLC Method for the Simultaneous Estimation of Atenolol and Amlodipine in Tablet Dosage Form - Haque, Md Ahsanul; Naznin, Asma; Kabir, ANM Hamidul; Hossain, Md Khalid; Islam, SM Ashraful (Dhaka University Journal of Pharmaceutical Sciences, 2011)
A simple, selective and rapid reversed phase high performance liquid chromatographic (RPHPLC) method for the analysis of atenolol and amlodipine in tablet has been developed and validated. The chromatographic system consisted of a LC-20 AT pump, SPD-20 A UV/visible detector. The separation was achieved from C18 column at ambient temperature with a mobile phase consisting of methanol-acetonitrile buffer (solution of ammonium acetate and sodium pentanesulphonate ratio, 55:10:35 v/v, PH=3.00 adjusted with phosphoric acid) at a flow rate of 1ml/min and the retention time was about 1.67 minutes for atenolol and 5.0 minutes for amlodipine. The method is selective and able to resolve drug peaks from formulation excipients. The peaks of atenolol and amlodipine were well separated (resolution 11.65). The calibration curves were linear over the concentration range of 80% to 120% (r2 = 0.999 for both the drugs). The proposed method is accurate with 100.72% recovery for atenolol and 99.44% recovery for amlodipine and precise (%RSD of intra day variation were 0.53-0.152 for atenolol and 0.067-1.518 for amlodipine and %RSD of inter day variation were 0.024-1.518 for atenolol and 0.034-1.518 for amlodipine). The method has been used to test market products (six brands) and potency was found within limit (99.02%- 100.02% for atenolol and 97.4%-100.4% for amlodipine). Therefore, this method can be used as a more convenient and efficient option for the analysis of atenolol and amlodipine in tablet dosage form. Key words: Atenolol; amlodipine; method validation; HPLC; quantitative analysis DOI: http://dx.doi.org/10.3329/dujps.v9i2.7898 Dhaka Univ. J. Pharm. Sci. 9(2): 131-138, 2010 (December)